Pengaruh Pola Asuh dan Asupan Gizi terhadap Kejadian Stunting pada Anak Usia Dini di Nagari Tanjung Bungo - Najmi .; Dhea Cahyani Fitri; Ferdi Endra Setiawan; Gema Zaky Yufrizal; Syalaisha Amani Fatiah; Yolanda Aprilia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Stunting in early childhood remains a major health concern in Nagari Tanjung Bungo, Kabupaten 50 Kota. This study aims to examine the influence of parenting patterns and nutritional intake on the incidence of stunting, as well as the role of Posyandu and the Community Service Program (KKN) in its prevention. Data were collected through monitoring child growth, interviews with families, and educational activities during KKN from June to July 2025. The results indicate that children with good parenting and balanced nutrition are less likely to experience stunting. Posyandu, as a community health service center, proved effective in raising awareness and supervising child development. However, challenges related to knowledge and access to nutritious food require further attention. Therefore, strengthening Posyandu’s role, community empowerment, and continuous education are crucial to reduce stunting rates in this area. This study provides valuable insights for improving parenting practices and nutrition for the better future of children.